Death from bongkrekic acid toxicity: first report in North America - Liz Eneida Rivera Blanco; David Kuai; Nicholas Titelbaum; Babar Fiza; David Reehl; Zakaa Hassan; Nader Dbouk; Alex J. Krotulski; Barry K. Logan; Sara E. Walton; Irene Liu; Michael Yu; et al. (Toxicology Communications, 2024)
Background Bongkrekic acid (BA) is a mitochondrial toxin, produced by the bacteria Burkholderia gladioli pv. cocovenenans during fermentation. Outbreaks of BA poisoning have been reported in China, Indonesia, and Mozambique, but have not been previously observed in North America.Case discussion A 67-year-old male with a past medical history of hypertension presented with two days of generalized weakness, nausea, and vomiting. He had consumed ogi, a home-fermented cornmeal pudding two days earlier. The patient developed acute liver failure, encephalopathy, acute kidney injury, coagulopathy, methemoglobinemia, and metabolic acidosis. Despite intensive care, he died on hospital day 8. Workup for common causes of acute liver failure was negative. Blood testing was positive for BA, estimated at 1,000 ng/mL. This case illustrates poisoning by BA, a rare and often lethal toxin resulting from improperly fermented food.